More Income Equality or Not? An Empirical Analysis of Individuals? Preferences - María A. García-Vali\~nas; Roberto Fernández Llera; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Do people prefer a society with an extensive social welfare system with high taxes, or low taxes but lax redistributive policies' Although economists have for a long time investigated the trade-off mechanism between equity and efficiency, surprisingly little information is available about citizens' preferences over the distribution of income in a society. The aim of this paper is reduce this shortcoming, investigating in an empirical study working with World Values Survey, what shapes individuals' preferences for income equality in Spain. We present evidence that not only traditional economic variables are relevant to be considered, but also factors such as ideology, political interest, fairness perception about others or trust in institutions, are key determinants to understand preferences towards redistribution and equality.
Keywords: H23; H53; I31; 330; redistribution; inequality; welfare state; social capital